Lithological, structural, and geochemical characteristics of the Mesoarchean Târtoq greenstone belt, South-West Greenland, and the Chugach-Prince William accretionary complex, southern Alaska: Evidence for uniformitarian plate-tectonic processes - Polat, Ali; Kokfelt, Thomas; Burke, Kevin C.; Kusky, Timothy; Bradley, Dwight; Dziggel, Annika; Kolb, Jochen (NRC Research Press (a division of Canadian Science Publishing), 2016)
The Mesoarchean Târtoq greenstone belt, South-West Greenland, consists of tectonically imbricated slices of metamorphosed basalt, gabbro, peridotite and sedimentary rocks, and is intruded by felsic rocks (now mylonites) with well-preserved duplex structures, representing a relict accretionary prism. The Târtoq greenstone belt is a remnant of a supra-subduction zone ophiolite that originated as back-arc basin oceanic crust. Following the initiation of intra-oceanic subduction, the back-arc oceanic crust accreted to the overriding plate, forming an accretionary prism. The felsic mylonites are compositionally akin to Archean tonalite-trondhjemite-granodiorite suites (TTG). Field observations, along with geochemical and zircon U-Pb age data, indicate that the protoliths of the felsic mylonites were derived from partial melting of back-arc basalts in the accretionary prism and emplaced along thrust faults between 3012±4 and 2993±6 Ma. It is proposed that the partial melting of the basalts likely occurred in response to ridge subduction. The Upper Cretaceous turbiditic greywackes of the Chugach-Prince William accretionary complex in southern Alaska are intruded by Paleogene felsic dykes. These felsic dykes appear to have been derived from partial melting of subducted and/or accreted oceanic crust during slab window magmatism. Archean granitoid-greenstone terrains share many geological characteristics of Phanerozoic subduction-accretion complexes such as the Alaskan and Altaid subduction accretion complexes, consistent with the operation of uniformitarian geological processes in the Archean. The Archean Earth might have been dominated by numerous smaller plates and greater ridge length than today that would have resulted in more frequent ridge-accretionary prism interactions and larger volumes of TTG generation in subduction-accretion complexes. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.